The Obsolescence of Man in The Digital Society - Maillard, Dominique (International Journal for Applied Information Management, 2021)
Commenting on the limitations of Man after the moral disasters of World War II and the logics of production inherent to the second industrial revolution, GuntherAnders had concluded to the “obsolescence of Man”. Anders pointed to the "Promethean gap" that exists between Man as an instrument among other instruments and his ability at encompassing the superior efficiency of the products he churned out. The new realities of production and trade, of human body engineering and power politics, as well as the shift from ownership to access, in the "digital society" hint that Gunther Anders's remark are still valid in the context of the third industrial revolution based on the Knowledge economy.